A Low Power Injection-Locked CDR Using 28 nm FDSOI Technology for Burst-Mode Applications - Yuqing Mao; Yoann Charlon; Yves Leduc; Gilles Jacquemod (Journal of Low Power Electronics and Applications, 2024)
In this paper, a low-power Injection-Locked Clock and Data Recovery (ILCDR) using a 28 nm Ultra-Thin Body and Box-Fully Depleted Silicon On Insulator (UTBB-FDSOI) technology is presented. The back-gate auto-biasing of UTBB-FDSOI transistors enables the creation of a Quadrature Ring Oscillator (QRO) reducing both size and power consumption compared to an LC tank oscillator. By injecting a digital signal into this circuit, we realize an Injection-Locked Oscillator (ILO) with low jitter. Thanks to the good performance of this oscillator, we propose a low-power ILCDR with fast locking time and low jitter for burst-mode applications. The main novelty consists of the implementation of a complementary QRO based on back-gate control using FDSOI technology to realize a simple and efficient ILCDR circuit. With a Pseudo-Random Binary Sequence (PRBS7) at 868 Mbps, the recovered clock jitter is 26.7 ps (2.3% UIp-p) and the recovered data jitter is 11.9 ps (1% UIp-p). With a 0.6 V power supply, the power consumption is 318μW. All the results presented here are based on post-layout simulations, as no prototypes have been produced. Similarly, we can estimate the surface area of the chip (without the pad ring) at around 6600 μm2.